The impact of negative affectivity, job satisfaction and interpersonal justice on workplace deviance in the private organizations - Alias, Mazni; Mohd Rasdi, Roziah; Abu Said, Al-Mansor (Universiti Putra Malaysia Press, 2012)
Workplace deviance has become pervasive in most organizations today. Researchers conceptualized workplace deviance based on whether the offence is directed towards organizational or interpersonal deviances. This study examined the contributions of individual and situational factors towards workplace deviance in the private organizations. Workplace deviance was conceptualized as interpersonal deviance and organizational deviance. Self-administered survey was conducted on 160 employees who worked full-time. The findings of the study indicated that negative affectivity and interpersonal justice were positively and significantly correlated with both types of workplace deviance, and the correlations were low. However, job satisfaction was not correlated with organizational deviance and interpersonal deviance. Implications and suggestions for future research are also discussed.